Epidemiological profile of maternal mortality - Ana Claudia Sierra Martins; Lélia Souza Silva
ABSTRACT Objective: To know the epidemiological profile of maternal mortality in Juiz de Fora, a city in the state of Minas Gerais. Data collection was carried out from April to December 2016. Method: Summary of a confidential investigation of maternal mortality on deaths occurred from January 1st, 2005 to December 31, 2015. Results: Eighty-five deaths of women residing in Juiz de Fora were identified and analyzed. The age group was between 20 and 36 years. The women carried out prenatal care (74.1%) with less than six visits (34.0%). Cesarean section was conducted in 38.8% of the childbirths and the obstetric treatment was considered appropriate (32.9%). The first cause of maternal death was hypovolemic shock 12 (14.10%), followed by uterine hypotony 6 (7.0%). Conclusion: Cesarean section rates are high and prenatal adherence is lower than that expected, which could justify the number of deaths in the period studied.